2021
DOI: 10.1371/journal.pntd.0009638
|View full text |Cite
|
Sign up to set email alerts
|

Sandfly Fever Sicilian Virus-Leishmania major co-infection modulates innate inflammatory response favoring myeloid cell infections and skin hyperinflammation

Abstract: Background The leishmaniases are a group of sandfly-transmitted diseases caused by species of the protozoan parasite, Leishmania. With an annual incidence of 1 million cases, 1 billion people living in Leishmania-endemic regions, and nearly 30,000 deaths each year, leishmaniasis is a major global public health concern. While phlebotomine sandflies are well-known as vectors of Leishmania, they are also the vectors of various phleboviruses, including Sandfly Fever Sicilian Virus (SFSV). Cutaneous leishmaniasis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…Particle size and concentration are among the most important indicators of purity of an EV sample. There are many studies reporting NTA for Leishmania EVs, and most of them have approximately similar size and concentration as reported in the present study (Lambertz et al, 2015;Barbosa et al, 2018;Douanne et al, 2020;Gioseffi et al, 2020;Nogueira et al, 2020;Heirwegh et al, 2021). One of the most similar studies on Leishmania EVs in terms of NTA results is done by Olivier et al and showed similar concentration and approximately similar size of EVs (Atayde et al, 2019).…”
Section: Discussionsupporting
confidence: 81%
“…Particle size and concentration are among the most important indicators of purity of an EV sample. There are many studies reporting NTA for Leishmania EVs, and most of them have approximately similar size and concentration as reported in the present study (Lambertz et al, 2015;Barbosa et al, 2018;Douanne et al, 2020;Gioseffi et al, 2020;Nogueira et al, 2020;Heirwegh et al, 2021). One of the most similar studies on Leishmania EVs in terms of NTA results is done by Olivier et al and showed similar concentration and approximately similar size of EVs (Atayde et al, 2019).…”
Section: Discussionsupporting
confidence: 81%
“…The LRV1 and the “exacerbatory” modules, that is, modules reflecting the effect of the presence of LRV1 on top of the presence of Leishmania , were identified and shown to represent a very considerable part of the overall transcriptomic change (representing together 53.3% and 42.5% at 8 and 24 h p.i.). The immunophenotype associated to the presence of LRV1, or to other viruses, was shown to be highly dependent on the systemic production of type I IFNs ( Rossi et al., 2017 ; Rossi and Fasel, 2018b ; Rath et al., 2019 ; Heirwegh et al., 2021 ). Although type I IFNs, such as IFN-α and IFN-β, are crucial for viral clearance, their influence during a Leishmania infection appears to be highly contextual.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the effect that virus can have go beyond LRV1 or the coadministration of phlebovirus during a sand fly bite. Mice challenged with a virus, such as LCMV, upon the resolution of Leishmania infection, led to a relapse of the Leishmania infection showing that exacerbation and the metastatic phenotype are not always linked to the presence of LRV1 ( Valencia et al., 2022 ) but could also be related to the presence of other viruses ( Rossi et al., 2017 ; Rath et al., 2019 ; Heirwegh et al., 2021 ). By exposing the modules and pathways affected by LRV1 as well as the hub genes responsible for driving such events, this study can contribute to the future design of strategies to deal with a Leishmania -viral coinfection.…”
Section: Discussionmentioning
confidence: 99%
“…Ellen Heirwegh et al, reported that Leishmania major with phleboviral infection was more infectious than L. major alone. A better understanding of the possible role of viral co-infection might lead to more effective treatment regimens [ 5 ]. One of the key challenges in the management of leishmaniasis and viral disease co-infection is the invention of a clinically effective treatment that not only treats leishmaniasis but also prevents viral disease.…”
Section: Introductionmentioning
confidence: 99%